2016
DOI: 10.1186/s40348-016-0065-3
|View full text |Cite
|
Sign up to set email alerts
|

Severe changes in colon epithelium in the Mecp2-null mouse model of Rett syndrome

Abstract: BackgroundRett syndrome is best known due to its severe and devastating symptoms in the central nervous system. It is produced by mutations affecting the Mecp2 gene that codes for a transcription factor. Nevertheless, evidence for MECP2 activity has been reported for tissues other than those of the central nervous system. Patients affected by Rett presented with intestinal affections whose origin is still not known. We have observed that the Mecp2-null mice presented with episodes of diarrhea, and decided to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…At the histological scale, Mecp2 -null mice displayed a shorter colon with severe changes in its epithelium similar to those observed in colitis and abnormal localization of key membrane proteins 31 . However, conditional deletion of Mecp2 from intestinal tissue using the villin promoter, an actin binding protein expressed mainly in the microvilli of the epithelium of the gut, does not reproduce the Mecp2 -null GI phenotype 31 . Since the conditional Mecp2-KO in non-neuronal cells does not display any body-weight decrease compared with the control group 8 , these symptoms may have a neural origin.…”
Section: Digestive Systemsupporting
confidence: 54%
“…At the histological scale, Mecp2 -null mice displayed a shorter colon with severe changes in its epithelium similar to those observed in colitis and abnormal localization of key membrane proteins 31 . However, conditional deletion of Mecp2 from intestinal tissue using the villin promoter, an actin binding protein expressed mainly in the microvilli of the epithelium of the gut, does not reproduce the Mecp2 -null GI phenotype 31 . Since the conditional Mecp2-KO in non-neuronal cells does not display any body-weight decrease compared with the control group 8 , these symptoms may have a neural origin.…”
Section: Digestive Systemsupporting
confidence: 54%
“…Furthermore, several colon-specific functions were related to extracellular matrix organization and integrin cell surface interactions, suggesting decreased interactions involved in focal adhesion and intestinal tissue polarization uniquely in the colon ( Supplementary Figure 9A ). The only function uniquely overrepresented in the ileum was transcriptional regulation by MECP2 ( Supplementary Figure 9A ), whose expression has been shown to play a role in intestinal morphology and function (Millar-Büchner et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…As the diets were similar between the Rett and control subjects, these results suggest that altered MECP2 levels in the digestive tract may alter the intestinal environment and thus microbe growth. In fact, it was recently shown that mice with loss of Mecp2 expression solely in the intestine have severe colonic epithelial defects (Millar-Büchner et al, 2016). As there is direct signaling from the gut to the brain, extension of these gut/microbiome studies should be extended to Bird Mecp2 −/+ deficient female deletion mice and would thus provide critical insights for female Rett patients.…”
Section: Mutations In Mecp2/mecp2 Affect Virtually All Organs and Tissuesmentioning
confidence: 99%